FORECASTING ANALYSIS OF TEH BOTOL PRODUCTS INVENTORY USING THE MOVING AVERAGE METHOD - Melda Agnes Manuhutu (LPPM Poltek ST Paul, 2021)
MSMEs in the supply of goods often experience problems in predicting the number of products that must be available for the following month. If the product is purchased in large quantities, it is feared that the product will not sell well. If the product is purchased in less quantity, the buyer may not get the item he needs. Based on the MSME problem situation, the researchers used the Weighted Moving Average or moving average method as a method to help forecast inventory for the next period, by looking for the smallest gala value to increase accuracy in forecasting the inventory of goods in the kiosk. The data used for this research is sales data for one year from 2020 to 2021. The Moving Average method is a method that gives different weights for each historical. This method produces inventory forecasts for the next period. Judging from the results obtained, namely the forecasting of the following period is 489 bottles. This forecasting result is very accurate because it is supported by the calculation result of the obtained MAPE value of 6.847%. Where, when the MAPE value is getting smaller, the more significant the forecasting accuracy is. With the analysis of inventory forecasting can help simplify the process of service owners in providing goods for the future